Predicting flows from the Dynamic Ergun Equation. (April 2017) - Tupper, G.B.; Govender, I.; Mainza, A.N.
Highlights: A basic question in dynamic beds is how to predict fluid flow. The Dynamic Ergun Equation is solved as a derivative expansion. First approximation is validated with PEPT data. Abstract: Positron Emission Particle Tracking observations of charge and slurry flow have shown that the pressure drop is effectively described by an Euler equation modified by a Darcy-like term. Here we consider the inverse problem: constructing and testing approximate solutions to the new Dynamic Ergun Equation. These solutions allow the prediction of transport in tumbling mills and other systems given information on the pressure drop and charge motion.